Fluorescent small organic probes for biosensing. Issue 10 (22nd February 2021) - Tian, Xue; Murfin, Lloyd C.; Wu, Luling; Lewis, Simon E.; James, Tony D.
Abstract : Small-molecule based fluorescent probes are increasingly important for the detection and imaging of biological signaling molecules due to their simplicity, high selectivity and sensitivity, whilst being non-invasive, and suitable for real-time analysis of living systems. Abstract : Small-molecule based fluorescent probes are increasingly important for the detection and imaging of biological signaling molecules due to their simplicity, high selectivity and sensitivity, whilst being non-invasive, and suitable for real-time analysis of living systems. With this perspective we highlight sensing mechanisms including Förster resonance energy transfer (FRET), intramolecular charge transfer (ICT), photoinduced electron transfer (PeT), excited state intramolecular proton transfer (ESIPT), aggregation induced emission (AIE) and multiple modality fluorescence approaches including dual/triple sensing mechanisms (DSM or TSM). Throughout the perspective we highlight the remaining challenges and suggest potential directions for development towards improved small-molecule fluorescent probes suitable for biosensing.